(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
This study uses the title of the village head in the implementation of development in the village of Tempok, Tompaso District. The focus of this study uses the theory of performance according to Gomes (2003: 134) suggests four indicators in measuring performance. This study used a qualitative method, informants of this study were 10 people taken from the Village Head, Village Secretary, Village Head, Head of Development, Chair of the Village Consultative Body, community members. Data collection uses interview, collection and arrangement techniques. the data analysis technique used in this qualitative research method is inductive proposed by Sugiyono. The results of this study are seen from 4 indicators, namely: (1) the work of the village head has been very good can be seen from the success of several implementation of development in accordance with community needs. (2) the quality of work in the implementation of development is quite good, it can be seen from the village head, as well as the liberation and direction of the village consultative body (BPD) and village officials. (3) the work knowledge of the village head is good in the eyes of the community because the village head is able to realize the development policies in accordance with what is needed by the community. (4) the cooperation of the village head is very good in the implementation of tasks can be seen from each process of carrying out the work, the village head always tries to move the community to work together to carry out the process of implementation of village development. Keywords : Village, Head Performance, Development.